AUTOANTIBODIES TO GLUTAMIC ACID DECARBOXYLASE AS A PATHOGENETIC MARKER OF TYPE I DIABETES MELLITUS - N. V. Piven; L. N. Lukhverchyk; A. I. Burakovsky; N. V. Polegenkaya; M. V. Karpovich (Медицинская иммунология)
Abstract. A new method of enzyme-linked immunosorbent assay (in solid-phase ELISA format) has been developed to determine concentrations of autoantibodies to glutamic acid decarboxylase, as well as an evidencebased methodology is proposed for its medical implications, as a quantitative pathogenetic predictive marker of autoimmune diagnostics in type 1 diabetes mellitus. This technique could be implied for serial production of diagnostic reagent kits, aimed for detection of autoantibodies to glutamic acid decarboxylase by means of ELISA approach. (Med. Immunol., 2011, vol. 13, N 2-3, pp 257-260)